SERK5 genetically compensates for the loss of BAK1 and BKK1 in regulating elf18-triggered immune signaling in Arabidopsis - Yujia Li; Yuheng Tao; Xinran Yao; Renqi Cao; Xiangyu Xiong; Ben-Qiang Gong; Jian-Feng Li (Proceedings of the National Academy of Sciences, 2025)
SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASEs (SERKs), particularly BRASSINOSTEROID INSENSITIVE1-ASSOCIATED KINASE 1 (BAK1) (SERK3) and BKK1 (SERK4), function as pleiotropic coreceptors to transduce extracellular developmental and immune signals in Arabidopsis thaliana . However, SERK5, the closest paralog of BAK1/BKK1, is long considered a nonfunctional kinase due to a mutation in the conserved arginine-aspartic acid (RD) motif within its kinase domain. Here, we show that artificial microRNA (amiRNA)-mediated cosilencing of BAK1 / BKK1 / SERK5 induces autoimmunity, which is more severe than that observed in bak1 bkk1 double mutants. Complementation with the amiRNA-resistant mSERK5 , but surprisingly not with mSERK5Km encoding an ATP-binding-deficient SERK5, rescues this autoimmunity. Knockout of ENHANCED DISEASE SUSCEPTIBILITY 1 , a central component of plant immunity with important functions in effector-triggered immunity (ETI), or BAK-TO-LIFE 2 , a surveillance protein sensing BAK1/BKK1 perturbations in immunity, partially suppresses the amiRNA-mediated autoimmunity. The bacterial elicitor elf18 swiftly upregulates SERK5 expression. BAK1 / BKK1 / SERK5 cosilencing seedlings complemented with mSERK5 maintain wild-type levels of elf18-induced mitogen-activated protein kinase (MAPK) activation, while overexpression of SERK5 , but not unrelated SERK1 or SERK2 , restores normal elf18-induced MAPK activation in bak1 null protoplasts. These findings unmask a substitute coreceptor role for SERK5 in elf18 signaling, and suggest that plants can monitor and discriminate between concurrent BAK1/BKK1/SERK5 inactivation and BAK1/BKK1 depletion to fine-tune the severity of downstream ETI responses.